Problematika Substansi Hukum Dalam Penegakan Hukum Pemilu - Sholihin, Misbakhus; Wibawa, Iskandar (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2023)
Election law enforcement is enforcing electoral justice through legal compliance. Law Number 7 of 2017 concerning General Elections, has been present as an election law regulation with Gakkumdu as an election criminal enforcer, but there are still problems in its implementation. The purpose of this study was to determine how the Law enforcement mechanism for the use of government facilities in Jepara Regency and the obstacles in terms of the legal substance of handling violations of the use of government facilities in Gakkumdu Jepara. The research method uses empirical juridical which emphasizes research in the field. The research site was Bawaslu Jepara. Interviews and distribution of questionnaires are data collection techniques. Data analysis techniques using qualitative data analysis techniques. The results showed that the law enforcement mechanism for the use of government facilities in Jepara regency used the election law and technical regulations of the general election supervisory board regulations. There is an obstacle factor in terms of substance lies in proving that the executor and campaign team must be registered with the KPU while the facts in the field are not registered and the handling period is at least 14 days.